Thermal buckling response of laminated and sandwich plates using refined 2-D models. (15th September 2017) - Vescovini, R.; D'Ottavio, M.; Dozio, L.; Polit, O.
Abstract: This paper discusses the thermal buckling analysis of composite plates and sandwich panels by means of a Ritz-based variable-kinematic formulation. Main feature of the proposed formulation consists in the representation of the structure by means of sublaminates, i.e. arbitrary groups of plies composing the panel. Each sublaminate is associated with an independent, arbitrary kinematic description, so that the use of refined, high-order theories can be restricted to specific regions, such as the core of sandwich panels. Monolithic plates can be studied as a special case where the structure is modeled using only one sublaminate. Presented are the critical temperatures, with and without accounting for the nonlinear pre-buckling effects, for a set of monolithic and sandwich configurations. When pre-buckling effects are neglected, the problem is solved as a standard eigenvalue problem. On the other hand, the introduction of pre-buckling effects leads to a nonlinear eigenvalue problem, which is solved with an iterative procedure. The results are validated against 3D solutions, and highlight the importance of accounting for pre-buckling deformations, especially in the case of sandwich panels. As demonstrated, high-fidelity predictions are obtained while keeping at minimum the amount of degrees of freedom.